Knowledge, attitudes and practices toward risk of basic nosocomial infection control among pediatric healthcare workers: a cross-sectional study in Nanjing, China - Yang, Ruizhe; Yan, Wu; Wang, Xu; Li, Wei; Xue, Shengfan; Wang, Tingting; Xiang, Xiaorong; Li, Qian (Frontiers in Public Health, 2025)
BackgroundThis study was conducted to systematically evaluate the knowledge, attitudes, and practices (KAP) of pediatric healthcare workers (HCWs) concerning risk assessment in basic nosocomial infection control, with a specific focus on identifying key demographic and professional variables that may influence these outcomes.MethodsA cross-sectional survey was conducted among 126 pediatric HCWs in Nanjing, China. A structured questionnaire on nosocomial infection control was developed using the Delphi method. Expert consensus was assessed using content validity indices (CVI) and Kendall's W. One-way ANOVA identified significant differences in responses to sub-questions. Factor analysis was based on severity and importance ratings. Linear regression examined associations between demographic variables and risk assessment performance. Statistical significance was defined as P < 0.05.ResultsOne-way ANOVA demonstrated statistically significant variations in responses to 17 sub-questions (P < 0.05), reflecting differing perceptions of severity and importance across departments. Factor analysis extracted two distinct factors related to severity (44.055, 29.767%) and one overarching factor associated with importance (51.505%). However, no statistically significant correlations were observed between age, gender, or professional title and knowledge levels regarding infection control, indicating minimal influence of these demographic characteristics on attitudes toward infection control practices.ConclusionThese findings provide key insights into current knowledge, attitudes, and practices regarding nosocomial infection control among pediatric HCWs in Nanjing, China. The observed differences between departments highlight the need for tailored interventions. Future research should focus on developing and evaluating such targeted strategies to improve infection control, patient safety, and care quality.